Meta-Analysis the Effectiveness of McKenzie Exercise to Reduce Pain in Patients with Non-Specific Low Back Pain - Sima Asmara Dewa Marya Mahardika Putri; Agus Kristiyanto; Hanung Prasetya (Journal of Epidemiology and Public Health, 2021)
Background: Low back pain (LBP) is defined as a symptom that cannot be specifically validated. LBP is one of the most common forms of musculoskeletal disorders. Anyone can experience lower back pain throughout his life, because LBP is back pain without any underlying abnormalities. There are many exercises that can be given to treat this LBP, one of which is the McKenzie Exercise. The principle of this exercise is to improve posture to reduce lumbar hyperlordosis. This study aims to analyze the effectiveness of the McKenzie Exercise for pain reduction in patients with non-specific LBP. Subjects and Method: This was a systematic review and meta-analysis carried out with the PRISM flow diagram. Search for articles through journal databases includes: PubMed, Science Direct, Google Schoolar and PEDro by selecting articles published in 2010-2020. The keywords used were ("LBP" OR "Low Back Pain") AND ("McKenzie Exercise" OR "Therapy") AND "randomized controlled trial". The inclusion criteria were full paper articles with the Randomized Controlled Trial (RCT), the size of the relationship used with the Mean SD, the intervention given was McKenzie Exercise, the study subjects had an age range of 18-65 years, and experienced non-specific low back pain, without radicular pain. Eligible articles were analyzed using the Revman 5.3. Results: A meta-analysis of 11 articles showed that the McKenzie Exercise was able to reduce pain in patients with non-specific low back pain by 0.44 times compared to other interventions or no intervention. (SMD -0.44; 95% CI = -1.06 to 0.18; p = 0.16).Conclusion: McKenzie Exercise has a weak effect to reduce pain in patients with non-specific low back pain.